Effects of Costa Concordia shipwreck on epiphytic assemblages and biotic features of Posidonia oceanica canopy. Issue 1 (15th August 2016) - Bacci, T.; Penna, M.; Rende, S.F.; Trabucco, B.; Gennaro, P.; Bertasi, F.; Marusso, V.; Grossi, L.; Cicero, A.M.
Abstract: This research provides first information about Posidonia oceanica canopy in the area affected by Costa Concordia wreck. Percentage cover of algal and animal taxa on the leaves was estimated and biotic features of the meadow were measured in the period just after the shipwreck until its removal from the impacted site. Changes in epiphytic assemblages and some biotic features were detected in the Disturbed site compared with Control ones, highlighting effects due to the wreck presence and activities related to its removal. A temporary decrease of encrusting macroalgae and an increase of erected macroalgae and foraminifers, as well as a temporary increase of tip erosion of the canopy were detected in the Disturbed site. The obtained results were discussed and hypotheses about possible synergic effects occurred near the wreck were commented. Highlights: The Costa Concordia shipwreck occurred in a highly protected area of Giglio Island. First information on effects of Costa Concordia event on P. oceanica meadow is shown. Results about epiphytic assemblages and biotic features of the canopy are discussed. Functional and ecological data suggest a reduced chemical pollution near the wreck. Possible synergic effects associated with wreck and its removal occurred.